Complete genome sequencing of a Tequintavirus bacteriophage with a broad host range against Salmonella Abortus equi isolates from donkeys - Liu, Wenhua; Han, Letian; Song, Peng; Sun, Huzhi; Zhang, Can; Zou, Ling; Cui, Jiaqi; Pan, Qiang; Ren, Huiying (Frontiers in Microbiology, 2022)
Salmonella enterica subspecies enterica serovar abortus equi (S. Abortus equi) is the most common cause of abortion in mares. It has recently been found to cause abortion in donkeys more frequently in China. A novel virulent bacteriophage vB_SabS_Sds2 (hereafter designated Sds2) was isolated from the feces of donkeys using a S. Abortus equi strain as host. Phage Sds2 had an isometric polyhedral head and an uncontracted long tail, belonging to the Tequintavirus, Markadamsvirinae, Demerecviridae, Caudovirales. The genome of phage Sds2 was 114,770 bp, with a GC content of 40.26%. The genome contained 160 open reading frames (ORFs), and no ORFs were associated with pathogenicity, drug resistance or lysogenization by sequence analysis. Both genome annotation and phylogenetic analysis indicated that phage Sds2 was highly similar to T5-like bacteriophages. Phage Sds2 could lyse 100% (30/30) of S. Abortus equi strains, 25.3% (24/95) of other serotypes of Salmonella strains and 27.6% (8/29) of E. coli strains using the double-layer agar plate method. The in vitro test showed that phage Sds2 had high bactericidal activity against S. Abortus equi at a wide range of MOIs. The in vivo test indicated that phage Sds2 had inhibitory effect on abortion in mice challenged with S. Abortus equi. In general, phage Sds2 is a novel lytic phage with a wide host range and has the potential to prevent abortion caused by S. Abortus equi.